Limitations, Legacies, and Lessons: Post-Katrina Rebuilding in Retrospect and Prospect. (September 2015) - Gotham, Kevin Fox
Over the past two decades, federal block grants and spatially targeted tax subsidies have become popular forms of federal assistance to disaster-affected areas. This article provides an overview and critical evaluation of the impact of the Gulf Opportunity Zone and the Community Development Block Grant–Disaster Recovery program in the years after Hurricane Katrina. I focus particular attention on the limitations, problems, and inequality reinforcing characteristics of the two programs. The experience in the Gulf South suggests that the effectiveness of the Community Development Block Grant program and spatially targeted tax incentives could be enhanced if policy makers build in clear rules and procedures for delivery of aid, enforce antidiscrimination statutes and fair housing laws, and exercise strong oversight over program implementation at the state and local levels. I conclude that the success of federal disaster recovery programs in realizing their recovery goals depends on political efforts to reduce class and racial inequalities and promote social justice.